Primary hydatidosis of psoas muscle: rare entity - Chincholkar, Rajesh G.; Tongale, Ram V. (International Surgery Journal, 2022)
Hydatid cyst of the psoas is uncommon to see. We hereby report a case of hydatid cyst of the psoas in a 22 years old female patient presented with pain and swelling in right lumber region. CECT abdomen revealed hydatid cyst indenting inferior pole of right kidney also indenting adjacent ascending colon and abutting right psoas muscle.